Aviation-Related Incidents: Psychological Effects to The Current and Future Student Pilots - Ken Reave Lowell R. Helit; Ryan Angelo B. Dela Cruz; Miguel Jericho Y. Divina; Gene Eduard A. Ducoy; Wreinner C. Escudero; Matt Andrei G. Genetia; John Philip Q. Obmasca; France Patrick S. Sumadsad; Marianne Shalimar G. Del Rosario (International Journal of Progressive Research in Science and Engineering, 2024)
This study aimed to identify and examine the psychological effects of the number of aviation-related incidents for current and future student pilots. This study includes specific problems regarding the level of knowledge on aviation-related incidents in the last decade and its most common type, the expected behaviors by the student pilots with knowledge of these incidents, the significant relationship of the behaviors and the aviation-related incidents, the significant differences among the respondents’ profile when grouped by age and their college course. Lastly, the reasons for the respondents' differences when grouped by their profiles. This study used a mixed-method approach which combines both quantitative and qualitative methods. The quantitative approach used in this study aimed to investigate and determine the psychological effects on student pilots by using survey questionnaires to gather and collect data. For the qualitative approach, an interview was conducted in this study to measure the student pilot’s insights about aviation-related incidents. The results showed consistent indications of differences in the level of knowledge among respondents and their exhibited behaviors when grouped according to the profiles, especially if grouped by age. In conclusion, the aviation industry is still as safe as it could be, showing no room for mistakes even if student pilots are faced with a lot of work-related stressors, their behavior does not affect the number of local aviation-related incidents. The researchers recommend a change in curricula for student pilots and create more specialized training to enhance knowledge of the different types of aviation-related incidents and to continue the overall safety of the aviation industry.